A didakhe kaine de Jesus: um ensaio exegético de Mc 1.21-28 - Lira, David Pessoa de (2006)
This present work is a result of a process of survey in the area of the Bible. This is a exegetical study of the New Teaching of Jesus based on the Gospel according to Saint Mark, chapter 1, verses 21 to 28. At the beginning, an analysis is done according to the steps of the historical critical method: translation of the original text, from Greek to the Vernacular Tongue; textual-criticism of a phraseology "didachê kainê kat exousían" [Greek]. And the literary criticism seeks to define the limits and the constitutive elements of the pericope; this first part of this work finishes with redaction criticism and form criticism. In the second part of this work, there is a survey about the historical environment of the times of Jesus: a survey of elements which belong to the story such as synagogue, Cafarnaum, scribes. And the relation of these elements with the tradition and the Law. The last part of this work presents some important characteristics of Jesus as teacher, showing the similarities and differences between the practice of teaching. In the same form, this part of this work presents the performance of Jesus through the Law and the traditions; finally, this part analyzes about what is the praxis of Jesus so that it deserves special regard and so that it is an example to the pratice of the teachers and popular educators today, just as the atualization presented proposes at the end of this work.